Performance of Seismic Restrainer with SMA Springs for Sliding Isolation of Single-Layer Spherical Lattice Shells - Peng Zhuang; Wenting Wang (Shock and Vibration)
The seismic response of a single-layer spherical lattice shell controlled by restorable sliding isolator is studied under different seismic excitations. The isolation system consists of flat steel-Teflon sliding isolators and superelastic SMA spring restrainers. The NiTi-SMA is used to fabricate helical spring for recentering control of the isolation system. In the first step of this investigation, the configuration scheme and functioning mechanism of a novel SMA spring restrainer are introduced briefly. Then, realistic mechanical behavior of large-scale superelastic NiTi helical spring is studied through a set of cyclic experimental tests. According to the obtained hysteresis loops, a mechanical model combining multilinear model and hysteresis model is developed to simulate the overall response of the SMA-based seismic restrainer. Besides, the sliding isolator is evaluated using a bilinear force-displacement hysteresis model. Finally, a 60 m span single-layer spherical lattice shell with substructure is modeled with finite element program. Nonlinear time history analyses of the controlled and uncontrolled lattice shell are performed considering multidimensional seismic inputs. The study shows that the seismic response of the controlled lattice shell can be effectively reduced by using isolation and control devices. Furthermore, the seismic response of the isolation system such as peak displacement and residual displacement can be effectively controlled by using the developed SMA spring restrainers.